PENERAPAN ANTI-DUMPING INTERNATIONAL TRADE COMMISSION AMERIKA DALAM KASUS PRESTRESSED CONCRETE STEEL WIRE STRAND INDONESIA BERDASARKAN GENERAL AGREEMENT ON TARIFFS AND TRADE: Application Of Anti-Dumping By The United States International Trade Commission In The Case Of Prestressed Concrete Steel Wire Strand From Indonesia Based On General Agreement Tariffs And Trade - Zaki Fachrezi; Rosdiana Saleh (Faculty of Law, Universitas Trisakti, 2025)
GATT (General Agreement on Tariffs and Trade) authorizes its member countries to take anti-dumping measures against imported products that enter with dumping practices to protect domestic producers and markets. However, the implementation of anti-dumping policies often does not work as it should. This can be seen in the case of the application of anti-dumping by the United States against preset pressed concrete steel wire strand products from Indonesia, which raises issues related to the suitability of the action with the provisions of the GATT and the legal steps that can be taken by Indonesia in the face of the dumping allegations. This research uses secondary data, so it is classified as normative research with a descriptive approach and uses a deductive inference method. USITC (United States International Trade Commission) stated that PT Bumi Steel Indonesia did not fully demonstrate the Best of Its Ability during the anti-dumping investigation process. The result and conclusion of this research shows that the application of Adverse Facts Available-based dumping margin is not in line with GATT provisions. The different interpretation of Best of Its Ability between USITC and PT Bumi Steel Indonesia, which refers to Articles 6.1 and 6.2 of the Anti-Dumping Agreement, caused PT Bumi Steel Indonesia to be subject to the highest dumping margin. As a legal measure, Indonesia may file a dispute under the provisions of the Dispute Settlement Understanding (DSU).